Do immigrants affect firm-specific wages? - Nikolaj Malchow-Møller; Jakob Roland Munch; Jan Rose Skaksen (Institute for the Study of Labor (IZA), 2007)
In this paper, we propose and test a novel effect of immigration on the wages of native workers. Existing studies have focused on the wage effects that result from changes in the aggregate labour supply in a competitive labour market. We argue that if labour markets are not fully competitive, the use of immigrants may also affect wage formation at the most disaggregate level - the workplace. Using linked employer-employee data, we find that an increased use of workers from less developed countries has a significantly negative effect on the wages of native workers at the workplace - also when controlling for potential endogeneity of the immigrant share using both fixed effects and IV. Additional evidence suggests that this effect works at least partly through a general effect on the wage norm in the firm of hiring employees with poor outside options (the immigrants).
Keywords: F22; 330; Immigration; firm-specific wages; outside options; Migranten; Ausländische Arbeitskräfte; Lohnbildung; Lohn; Dänemark